Analysis of the Implementation of SAKTI on Bill Settlement Performance (Case Study at BMKG) - A. Fajar Trijanuardi; Machmudin Eka Prasetya (Green Publisher Indonesia, 2025)
The full implementation of the SAKTI system across all Ministries/Institutions in 2022—following its pilot testing since 2015—is part of the realization of the Integrated Financial Management System concept. This research aims to assess the relationship between the implementation of the SAKTI system and bill settlement performance, which is a component of the budget execution performance assessment (IKPA), through a case study at BMKG. The study was conducted using the Human-Organization-Technology Fit (HOT-Fit) Model framework to evaluate the success of SAKTI. A qualitative research method was employed, with data collected through interviews and questionnaires distributed to respondents who are users of the SAKTI commitment and payment modules. The results of this study show that the implementation of SAKTI is directly associated with improvements in bill settlement performance. These improvements include increased efficiency in the time required to complete the billing process, enhanced data accuracy through system integration across related modules, improved collaboration among involved teams, and more secure data handling and usage. Overall, SAKTI supports faster, more accurate, and more efficient bill settlement, thereby contributing to better performance in government agency budget implementation—despite ongoing technical challenges and system instability, particularly during maintenance periods and high-usage times.